How Self-Efficacy Drives Job Performance: The Role Of Job Anxiety And Intrinsic Motivation - Nurlaely Razak (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2022)
This study seeks to investigate self-efficacy on job performance through the role of work anxiety and intrinsic motivation. The research sample consisted of 83 employees and ten leaders on the STIEM Bongaya campus, and data analysis used Warp PLS 7.0. This study does not support the hypothesis that the better the self-efficacy, the higher the job performance. So, as a practical implication, self-efficacy is not the main determining factor in determining the value of job performance in tertiary institutions. Interestingly, self-efficacy has a positive and significant effect on work anxiety, and subsequently, job performance is getting better. It was found that the better the self-efficacy, the better the intrinsic motivation, and the better job performance. Hence, the role of work anxiety and intrinsic motivation as a complete mediation variable. The higher the self-efficacy, the higher the anxiety and the higher the job performance, but the impact is not significant or significant. Furthermore, the better the self-efficacy, the higher the intrinsic motivation and higher job performance, but the impact is not significant.